2020
DOI: 10.3390/jpm10030097
|View full text |Cite
|
Sign up to set email alerts
|

Benefit of Wearing an Activity Tracker in Sarcoidosis

Abstract: Sarcoidosis causes many disabling symptoms, including fatigue and exercise limitations, which have been shown to improve by physical activity programs. The aim of this study was to estimate the effect of continuous activity monitoring using an electronic activity tracker (AT) on exercise performance and fatigue of sarcoidosis patients, compared to controls (cohort study), and the effect of additional personal coaching (randomized trial) over a period of 3 months. Fifty-four sarcoidosis patients received an AT … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 17 publications
(8 citation statements)
references
References 39 publications
(57 reference statements)
0
8
0
Order By: Relevance
“…Notably, three-quarters of HCPs would like to monitor physical activity levels, which is done infrequently in current practice. Until now, few studies have evaluated the use of physical activity trackers in ILD (11)(12)(13). Physical activity trackers may be useful to monitor and predict disease deterioration over time, encourage patients to exercise, and enable tele-rehabilitation (11)(12)(13).…”
mentioning
confidence: 99%
“…Notably, three-quarters of HCPs would like to monitor physical activity levels, which is done infrequently in current practice. Until now, few studies have evaluated the use of physical activity trackers in ILD (11)(12)(13). Physical activity trackers may be useful to monitor and predict disease deterioration over time, encourage patients to exercise, and enable tele-rehabilitation (11)(12)(13).…”
mentioning
confidence: 99%
“…These two variables were investigated before and have shown promising results. 41 We believe that telehealth may potentially provide a valuable way of supporting both physiological and psychological needs of patients with ILD.…”
Section: Discussionmentioning
confidence: 99%
“…Consumer-level activity trackers (e.g., Fitbit, San Francisco, CA, United States) can record multiple parameters including step counts, heart rate, heart rate variability, SpO2, and skin temperature. Data from a small study in sarcoidosis reported an improvement in exercise performance in patients wearing an activity tracker compared to controls ( 33 ). Perceived positive effects may drive many patients to self-initiate activity monitoring using wearables.…”
Section: Current and Future Directionsmentioning
confidence: 99%